2019
DOI: 10.3390/ijerph16245150
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress, Sedentary Behavior, and Physical Activity during Pregnancy among Canadian Women: Relationships in a Diverse Cohort and a Nationwide Sample

Abstract: Background: Past research shows that psychosocial stress and distress predict sedentary behavior and physical activity, but few studies focus on pregnant women. Our objective was to analyze relationships between psychosocial stress and distress with sedentary behavior and physical activity among pregnant women in Canada. Methods: We analyzed objectively-measured sedentary behavior and physical activity at 16–18, 24–26, and 32–24 weeks pregnancy in a sociodemographically diverse cohort of 70 women in Montreal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Moreover, PA helps to maintain-or increases-cardiovascular endurance, muscle strength, resistance, agility, coordination, and equilibrium [5,11,18] and reduces the impact of muscle-skeletal pain such as backache [19]. The emotional benefits of PA include the strengthening of one's mood and self-esteem, increased sleep quality [3,20], and decreased stress during pregnancy [21].…”
Section: Physical Activity During Pregnancy: On Guidelines Performanmentioning
confidence: 99%
“…Moreover, PA helps to maintain-or increases-cardiovascular endurance, muscle strength, resistance, agility, coordination, and equilibrium [5,11,18] and reduces the impact of muscle-skeletal pain such as backache [19]. The emotional benefits of PA include the strengthening of one's mood and self-esteem, increased sleep quality [3,20], and decreased stress during pregnancy [21].…”
Section: Physical Activity During Pregnancy: On Guidelines Performanmentioning
confidence: 99%
“…For reasons of exercise controversy and antenatal taboos, around 80% of pregnant women worldwide are physically inactive, especially in the last trimester of pregnancy. 11,15,16 In recent years, growing evidence in western countries has demonstrated that physical exercise during pregnancy is beneficial to women with GDM, and could lower the glucose level and reduce the risk of adverse perinatal outcome, [1][2][3][4]11 but evidence on the association of physical exercise during pregnancy and glycemic control among women with GDM is still limited in China.…”
Section: Introductionmentioning
confidence: 99%
“…There has always been a controversy about exercising during pregnancy [ 16 ]. For this reason, around 80% of pregnant women are physically inactive, increasing this inactivity during the last trimester of pregnancy [ 17 ]. However, today it is known that there are many benefits that exercise offers to both the fetus and the mother.…”
Section: Introductionmentioning
confidence: 99%